Development and Standardization of a Scale to Measure Vegetable Growers’ Attitude towards Safety Measures in Pesticide Application - Singh, Prashish; Ghadei, Kalyan; Roy, Shubhadeep; Halder, Jaydeep; Kumari, Jagriti; Paliwal, Harshit (Indian Journal of Extension Education, 2025)
The study aimed to develop a scale for assessing the attitude of vegetable growers towards safety measures in pesticide application was conducted during 2024. A total of 110 statements were initially framed under eleven dimensions: Selection and Transportation, Storage, Precautions during Preparation and Application, Precautions after Application, Disposal of Containers, Environmental Protection, Health and Safety, Record Keeping and Monitoring, Pesticide Regulations, Education and Training, and First Aid and Emergency Response. These were evaluated by 60 judges, based on their judgment and subsequent item analysis, 52 statements were retained after calculating the t-values. The scale was constructed using the Likert methodology, yielding an overall mean relevancy score of 2.50. A pilot test was conducted with 60 vegetable growers from a non-sampled area, setting the cut off value for item selection at equal or more than 1.75 t-value. Reliability was assessed using the split half method, which yielded a coefficient value of 0.82. This result was further verified using the Spearman-Brown formula, producing a value of 0.89, thereby confirming the reliability of the scale. In addition, the Cronbach’s alpha value of 0.86 indicated a high level of internal consistency in the developed scale.
Keywords: Attitude; Disposal of container; Pesticide regulations; First aid; Record keeping and monitoring